Proteomic changes in the cortex membrane fraction of genetic absence epilepsy rats from Strasbourg - (:unkn) unknown (IMR PRESS, 2014)
Epilepsy is a serious neurodegenerative disorder with a high incidence and a variety of presentations and causes. Studies on brain from various animal models including chronic models: Genetic Absence Epilepsy Rats from Strasbourg (GAERS) are very useful for understanding the fundamental mechanisms associated with human epilepsy. Individual regions of the brain have different protein composition in different conditions. Therefore, proteomic analyses of the brain compartments are preferred for the development of new therapeutic targets in different pathophysiological conditions like neurodegenerative disorders. In this study, we describe a proteomic profiling of membrane fraction of cortex tissue from epileptic GAERS and non-epileptic Wistar rat brain by two-dimensional gel electrophoresis coupled with matrix-assisted laser desorption/ionization mass spectroscopy. Comparing the optical density of spots between groups, we found that one protein expression was significantly down-regulated (guanine nucleotide-binding protein G(I)/G(S)/G(T) subunit beta-1) and one protein expression was significantly up-regulated (14-3-3 protein epsilon isoform) in GAERS group. Our results indicate that these proteins might have played a significant role in epilepsy and may be considered as valuable therapeutic targets in the absence of epilepsy.
Keywords: Guanine nucleotide binding protein; 14-3-3 epsilon; proteome; epilepsy; rodent model; 14-3-3 PROTEINS; 2-DIMENSIONAL ELECTROPHORESIS; POLYACRYLAMIDE-GELS; CEREBROSPINAL-FLUID; ISOFORM; SEIZURES; EXPRESSION; HIPPOCAMPUS; MECHANISMS; THALAMUS